CCNA ICND2 200-105 exam prep : video - Odom, Wendell (LiveLessons (Indianapolis, Ind.), 2017)
CCNA ICND2 200-105 Exam Prep LiveLessons provides more than 10 hours of video training detailing common exam traps, pitfalls, and difficulties on the Cisco CCNA Routing and Switching 200-125 exam and the ICND2 200-105 exam. This title is focused on giving you the tools you need to pass the exam. Features include background information on the exam, a deep dive into common mistakes and misunderstandings people make when taking the exam, and an exam walkthrough with sample questions so you can see firsthand the types of questions you’ll encounter in the testing facility. Best-selling author and expert instructor Wendell Odom explores essential information about the exam, such as what to do if you get stuck on a question, what to expect in the testing facility, and how to manage your time. Module 2 is dedicated to helping you preemptively learn about common misunderstandings people make about the exam and also focus in on commonplace mistakes that people make. Module 3 takes you on a deep dive into the types of questions you’ll encounter for each domain in the exam. In this section you will have the opportunity to assess sample questions and see firsthand how the author solves each one while detailing why the right answer is correct and how to avoid pitfalls. This course is meant to help you prepare for the exam and identify areas of weakness, while improving your conceptual knowledge and hands-on skills.